2018
DOI: 10.1371/journal.pntd.0006628
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid protein-based vaccine provides protection in mice against lethal Crimean-Congo hemorrhagic fever virus challenge

Abstract: Crimean-Congo hemorrhagic fever (CCHF) is an acute, often fatal viral disease characterized by rapid onset of febrile symptoms followed by hemorrhagic manifestations. The etiologic agent, CCHF orthonairovirus (CCHFV), can infect several mammals in nature but only seems to cause clinical disease in humans. Over the past two decades there has been an increase in total number of CCHF case reports, including imported CCHF patients, and an expansion of CCHF endemic areas. Despite its increased public health burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…In this study, we have evaluated an eukaryotic expression vector (pVAX-1) expressing antibodies have no in vitro neutralizing activity. These findings do not undermine N as a vaccine target as it has been previously documented in animal models that non-neutralizing antibodies could protect mice model from lethal challenges [3,6]. A similar phenomenon was also described in influenza vaccine studies with animals, where protective anti-influenza immunity is attained in the absence of measurable neutralizing antibodies [29].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, we have evaluated an eukaryotic expression vector (pVAX-1) expressing antibodies have no in vitro neutralizing activity. These findings do not undermine N as a vaccine target as it has been previously documented in animal models that non-neutralizing antibodies could protect mice model from lethal challenges [3,6]. A similar phenomenon was also described in influenza vaccine studies with animals, where protective anti-influenza immunity is attained in the absence of measurable neutralizing antibodies [29].…”
Section: Discussionsupporting
confidence: 80%
“…The vectors [5][6][7]. It is also important to assess probable correlation between challenge protection and CD4 + and CD8 + responses [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another vaccine candidate, an adenovirus‐based vaccine expressing the CCHF nucleoprotein, protected an immunocompromised mice model against CCHF virus challenge; thus, adenoviral vectors are thought to be suitable for CCHV vaccines (Zivcec et al . 2018). A draft CCHF research and development road‐map charted by the WHO (2018) prioritized the most suitable CCHF vaccine candidates to enter clinical trials by 2019.…”
Section: Crimean–congo Hemorrhagic Fever Virusmentioning
confidence: 99%
“…Although the glycoproteins of CCHFV exhibit the greatest genetic diversity, we detected sustained CCHFV-specific T-cell responses against the more-conserved CCHFV nucleoprotein. Vaccine-induced responses solely against the nucleoprotein can be protective (24,25), and it is therefore likely that immune responses against the more-conserved CCHFV nucleoprotein could provide cross protection. Studies with monoclonal antibodies against the glycoproteins have shown that although there exist antigenic differences among diverse strains of CCHFV, there are neutralizing epitopes conserved among divergent strains (26,27).…”
Section: Figmentioning
confidence: 99%